KEBIJAKAN FORMULASI HUKUM DALAM PEMBERIAN PEMBEBASAN BERSYARAT BAGI NARAPIDANA YANG MELAKUKAN PENGULANGAN TINDAK PIDANA - Tri Aisyah; Dessy Artina; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Parole is the process of the construction of the prisoners outside the correctional after undergoing 2/3(two-thirds) of at least 9 months criminal period. In granting parole inmates must meet the specifiedrequirements, and there is also a trial period which must be met by the inmates, when inmates violate then hisexemption can be revoked and must live the remainder of the punishment has yet to be lived, his own parolecontained in Article 15 of the BOOK of law CRIMINAL LAW up to Chapter 16 of the BOOK of lawCRIMINAL LAW and in Article 14 of the letter K Act No. 12 of 1995 Correctional settings, and furthermorecontained in the Regulation of the Minister of Justice and human rights no. 3 Year 2018 on the terms andprocedures for the implementation of cultural assimilation, on leave visiting family, leave towards the free,Conditional Parole and Furlough.One of the problems occurred regarding the granting of parole is the absence of a clear settings andrestrictions in granting parole against inmates who do the repetition of criminal acts (residivis), which iscontained in the regulations.This research uses the normative or legal research typology also called with aparticular doctrinal legal research discusses the legal basis of despair. In the study authors use researchdeskriktif properties, because the author describes the policy formulation of the law in granting parole toinmates who do the repetition of criminal acts.The results of the research conducted by the author is there is a lack of clarity and restrictions ingranting parole against inmates who do the repetition of criminal acts. The absence of a clear arrangementmakes the inmates such as pleasantness and no deterrent in doing the repetition of criminal acts. so it needs tobe established and regulations clearly and logically as well as ideal in granting parole against inmates whodo the repetition of criminal acts. This is necessary in order to create legal certainty for inmates who aredoing the repetition of criminal acts.Keywords: Policy formulation, Parole, Recidivis.